The Impact of Google Docs–Mediated Electronic Feedback on Students’ Academic Writing - Amrizal; Henni Zuraidah; Nur Hasanah; Nikmatul Wahidah (Yayasan pendidikan dzurriyatul Quran, 2026)
This study seeks to investigate the role of Google Docs–facilitated electronic feedback in enhancing students’ academic writing skills within a higher-education context. Using a qualitative descriptive methodology, the study engaged 20 undergraduate students enrolled in an academic writing course. The data were gathered via semi-structured interviews, reflective journals, and document analysis of students’ writing drafts. The results show that students found electronic feedback helpful in improving the quality of their writing, particularly in organization, clarity, and grammar. Using Google Docs also made students more likely to revise their work multiple times, got them more involved in their learning, and gave them more freedom to learn on their own. Students engaged with the comments and exhibited greater awareness of their writing strengths and weaknesses. However, problems with limited access to technology and varying levels of digital literacy were also identified. The study demonstrates that Google Docs–mediated feedback provides significant and effective support for enhancing academic writing when used with appropriate pedagogical guidance across diverse learning environments.